Quo Vadis Implementasi Pemenuhan Hak Restitusi dan Hak Kompensasi Terhadap Korban Tindak Pidana - Bismillahi, Abda Oe (Southeast Asian Journal of Victimology, 2023)
The legal position of victims of crime is not recognized in the criminal justice system. Including the right to obtain compensation through the criminal justice system. Because the issue of compensation is a matter of the individual victim and this problem becomes the scope of civil law. This research wants to examine the technical settlement of fulfilling the right of restitution and compensation rights to victims of criminal acts based on the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2022 concerning Procedures for Requesting and Granting Restitution and Compensation to Victims of Crime, so that fulfillment of victims' rights can be realized through the criminal justice system. The approach method used in this research is normative legal research method. Normative legal research places law as a building system of norms. The results of the study show that Supreme Court Regulation Number 1 of 2022 is a practical policy that includes adjustments to laws and regulations, government decisions, judge decisions, the legal system and legal principles with the aim of increasing legal unity, legal certainty, justice (justice, gerechtigheid) and comparability (equit, billijkeid) thereby providing a new position for victims in the criminal justice system.